Intensi Berwirausaha Mahasiswa Berdasarkan Ciri Anggadiredja dan Djajamihardja - Inayati, Siti Reuni; Ihwandi, Lalu Rizal (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to determine how high the entrepreneurial intention of Gunung Rinjani University students is based on the characteristics of Anggadiredja and Djajamihardja. This type of research is quantitative research with descriptive statistical analysis techniques. Collecting data using a questionnaire with 150 students as respondents. To find out the high and low value of entrepreneurship intention in the students, the researcher used a categorization based on a hypothetical mean. From the results of a questionnaire of 150 respondents, the average score for 12 entrepreneurial traits according to Anggadiredja and Djajamihardja, first is Having Emotions to Imagine Success or Fear of Failure of 25.87, second Dare to Take Risks the average is 25.59, third Persevering and Working Hard the average value is 25.52 , the four Enthusiasm and Agile (Mobile) the average score is 25.37, the fifth Requires Feedback the average value is 25.37, the sixth is Personally Responsible for His Actions and Decisions the average value is 26.49, the Belief in Himself trait is obtained an average of 25.54, the eighth Have Broad Knowledge obtained an average of 25.22, the ninth Ability To Inspiring the average value of 24.47, the tenth Leadership Skills the average value of 25.03, the eleventh Innovators (Innovators) the average value of 25.54 and the twelfth Pursuit of Success the average value of 25.97. So it can be concluded that the entrepreneurial intention of each respondent is at a moderate level because it is in the range of values between 19-28.5.